PENGUATAN MANAJEMEN KEUANGAN BUMDES PANCA BHUANA MANDIRI DENGAN MENGGUNAKAN APLIKASI SIAPIK - Putu Trisna Windika Pratiwi, Ni; Sangging, Komang Ayu Pradnya Lestari; Maswari, Ni Luh Putu Elisa; Werdhiyanti, Ni Putu Putri Ayu; Eraviati, Albertina (Dharma Bhakti, 2024)
Mekar Bhuwana is a village/sub-district in Abiansemal District, Badung Regency, Bali Province, Indonesia. This village is the result of the expansion of Mambal Village, into Mambal Village in the west and Mekar Bhuwana Village in the east. Mekar Bhuana Village has stunning natural landscapes, beautiful hills, and holds great potential in forming a superior and prosperous young generation. To be able to realize this, the resources owned by the village must be utilized, and one of the doors to realizing community welfare in the economic sector is through BUMDes. BUMDes is a village business managed by the local government and has a legal entity. It could be said that BUMDes is a business entity whose capital is entirely or mostly owned by the village through direct participation originating from its own wealth. In carrying out daily business, of course BUMDes Panca Bhuana Mandiri requires an optimal recording system that can be used by even people who are unfamiliar with technology. And the SIAPIK application is one of the software that we will teach to BUMDes Panca Bhuana Mandiri. Strengthening BUMDes Financial Management begins with conducting an analysis in the form of an analysis of BUMDes Mekar Bhuana, coordinating with the leadership and staff of BUMDes Panca Bhuana Mandiri regarding training in using the SIAPIK application, and preparing the SIAPIK application for use at BUMDes Panca Bhuana Mandiri.